Analisis Mutu Briket Berbahan Baku Campuran Ampas Teh dan Sekam Padi Menggunakan Perekat Molase Menggunakan Metode Pirolisis - Nur Faizin; Reynadi Febri Afiandi; Zeni Ulma (Journal of Sustainable Energy Development, 2023)
This study aims to anayze the effect of molasses adhesive composition on the quaity of briquettes made from tea dregs and rice husks and to determine the characteristics of tea dregs and rice husk briquettes using molasses adhesive. The research was carried out through severa stages, namely the preparation of raw materias, drying of raw materias, pyrolysis of rice husks and tea dregs, raw materias mashed with a 40 mesh sieve, mixing of molasses adhesive, printing, drying and testing the characteristics of briquettes. The pyrolysis process takes 1 hour for the preparation of rice husks and 1.5 hours for the preparation of tea dregs with no or little air. The results showed that the best composition was TSM2 with a ratio of 30% tea dregs and 70% rice husks. The results of the study with the best composition, namely TSM2, caorific vaue 3771 ca/g, moisture content 9.28%, ash content 6.92%, density 1.16 g/cm3, kamba density 0.49 g/cm3, combustion rate 0.031 g/ s. TSM1 10% tea dregs charcoa and 90% rice husk charcoa caorific vaue 3399 ca/g, moisture content 8.94%, ash content 8.02%, density 1.51 g/cm3, kamba density 0.53 g/cm3, burning rate of 0.049 g/s and TSM3 50% tea dregs charcoa and 50% rice husk charcoa caorific vaue 4192 ca/g, moisture content 9.98%, ash content 6.85%, density 0.86 g/cm3, kamba density 0.43 g/cm3, the combustion rate is 0.025 g/s.